2016
DOI: 10.1186/s13018-016-0446-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of the supercapsular percutaneously assisted total hip approach for femoral neck fractures: surgical technique and case series

Abstract: BackgroundFemoral neck fractures are common injuries in the geriatric population associated with high morbidity and mortality rates. Studies have shown outcomes can be positively influenced by early postoperative mobilization. The supercapsular percutaneously assisted total hip (SuperPath) surgical technique has been shown to lead to early mobilization for osteoarthritic total hip replacement patients and as such has the potential to provide similar benefits in fracture patients. This manuscript provides a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Our data supported Bodrogi’s conclusion that the SuperPath approach allows for tissue sparing through preservation of external rotators, minimizing stretching of the gluteus medius, and reducing postoperative pain. These improvements likely lead to decreased postoperative narcotics usage and enhanced postoperative abductor strength and fast recovery that may all contribute to shortened hospital stays [ 18 ]. Subjects’ hip muscle activity ability was evaluated by TUG and TSC, which showed obvious improvement in walking speed and climbing ability in the SuperPath group, which could be biomechanically related to less impairment of hip muscles [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data supported Bodrogi’s conclusion that the SuperPath approach allows for tissue sparing through preservation of external rotators, minimizing stretching of the gluteus medius, and reducing postoperative pain. These improvements likely lead to decreased postoperative narcotics usage and enhanced postoperative abductor strength and fast recovery that may all contribute to shortened hospital stays [ 18 ]. Subjects’ hip muscle activity ability was evaluated by TUG and TSC, which showed obvious improvement in walking speed and climbing ability in the SuperPath group, which could be biomechanically related to less impairment of hip muscles [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early reports of the SuperPATH technique for elective THA have demonstrated early mobilization, short hospital stay, and low rates of dislocation and other complications [29] , [30] . A recent case series demonstrated feasibility of the approach for hemiarthroplasty, but there are little data on use of this approach for THA for femoral neck fractures [31] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above discussion, SuperPATH technology improved patient satisfaction in the early postoperative period. Bodrogi AW et al [31] performed the SuperPATH technique in 17 patients with femoral neck fractures. By clinical follow-up, they found that postoperative analgesia dosage was reduced and the hospital stays were shortened.…”
Section: Discussionmentioning
confidence: 99%